Trends in Cloud Computing-Based Information System Development: A Literature Review - Agustini, Sherly (Engineering and Technology International Journal, 2025)
Cloud Computing has rapidly evolved into a key technology supporting modern information systems. Its ability to provide flexible data storage, management, and access via the internet has made it a preferred solution across various sectors, including business, education, healthcare, and government. The widespread adoption of Cloud Computing is driven by its potential to reduce operational costs, enhance scalability, and improve system reliability. However, despite these advantages, significant challenges remain, particularly regarding data security, privacy, resource management, and system integration. The reliance on third-party service providers raises concerns about data breaches and cyber threats, necessitating continuous advancements in security technologies such as blockchain and artificial intelligence (AI). This study conducts a comprehensive literature review to analyze the latest developments in Cloud Computing, identifying key trends, challenges, and future opportunities. The findings suggest that while Cloud Computing continues to offer transformative benefits, addressing its security and management challenges is crucial for its optimal implementation. Future advancements in AI-driven security solutions and system efficiency optimizations are expected to further enhance Cloud Computing’s role in modern information systems.